Q: What is 3x 3y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The slope is -1. 3x+3y=12 Subtract 3x 3y=-3x+12 Divide by 3 y=-x+4

2X + 3X + 3Y ???= 5X + 3Y===============yes, addition of these monomials yields that answer

Using the elimination method, 3x + (2y) times 18x - 3y - 5 gives the result of 36xy + 3x - 3y - 5.

3x-3y

3x + 3 (y-z)

Related questions

There is not an answer but you can factor it.3x+3y=3(x+y)

3x-3y?

6

The slope is -1. 3x+3y=12 Subtract 3x 3y=-3x+12 Divide by 3 y=-x+4

2X + 3X + 3Y ???= 5X + 3Y===============yes, addition of these monomials yields that answer

6x-3y

Using the elimination method, 3x + (2y) times 18x - 3y - 5 gives the result of 36xy + 3x - 3y - 5.

This is like aÂ² - bÂ², with a = 9xÂ² and b = 9yÂ². This can be factored as (a - b)(a + b), then substitute for a & b: (9xÂ² - 9yÂ²)(9xÂ² + 9yÂ²), then (9xÂ² - 9yÂ²) can factor to (3x - 3y)(3x + 3y) so we have: (3x - 3y)(3x + 3y)(9xÂ² + 9yÂ²)

3x-3y

3x + 3 (y-z)

(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2

(14x-2y)+(7x-3y)+(-3x) = 14x-2y+7x-3y-3x =(14+7-3)x-(2+3)y =18x-5y